Un laboratorio de silicio: química sin reactivos - Benites Galbiati, Martín (Pontificia Universidad Católica del Perú, 2013)
The 2013 Nobel Prize in chemistry was awarded to A.Warshel, M.Levitt and M.Karplus for their contribution to the development of hybrid methods for computational chemistry. In this article a brief introduction about computational chemistry methods is presented. This paper will show the order in which the QM/MM (Quantum Mechanics/Molecular Mechanics) methods were developed for the study of macromolecular systems and specially their application in enzymes and biochemistry. Finally, the reach and future prospects of these methods originally developed by A. Warshel, M.Levitt and M. Karplus in the seventies will be discussed.

El Premio Nobel de Química de 2013 ha sido otorgado a A. Warshel, M. Levitt y M. Karplus debido al desarrollo de métodos híbridos de cálculo para química computacional. En este artículo se presentará una breve introducción del uso de los métodos de química computacional. Se describirá cómo se desarrollaron, y por qué, los métodos híbridos de cálculo, conocidos como QM/MM (Quantum Mechanics/Molecular Mechanics) para el estudio de sistemas macromoleculares, sobre todo para el caso de su aplicación en enzimas y bioquímica. Finalmente, se comentarán los alcances y expectativas futuras para estos métodos, desarrollados en los años 70.
A silicon laboratory: chemistry without chemicals
Keywords: Química Computacional; QM/MM; Premio Nobel; https://purl.org/pe-repo/ocde/ford#1.04.00